A designed model of urinary stone formation and the effect of Lapis judaicus on urinary parameters in rat - Mohammad Khoshnoud; Pouya Faridi; Reza Setayesh; Bahareh Baniani; Amir Reza Dehghanian (Shiraz University of Medical Sciences, 2023)
Urinary stones after urinary tract infections and prostate disorders are the third most common urinary tract diseases. In recent years various herbal medicines for preventing or treating renal stones have been marketed and may be helpful in prevention and treatment, but still effectiveness and safe drug therapy without surgical intervention is controversial. This study aimed to evaluate the effects of L. judaicus in the treatment of urinary stones. In order to form stone in an animal model, 1% Ethylene Glycol (EG) dissolved in drinking water was used. Forty rats were divided into eight groups. After 45 days of drug administration, to determine the effects of the drug on urinary and serum parameters, 24-hour urine and blood samples were obtained. Then animals were sacrificed and kidneys were sent to the pathology laboratory for histological examination. Results of our study showed that prescribing L. judaicus in the co-treatment group reduced serum BUN, elevated urinary citrate and urine pH, and reduced urinary parameters such as urine protein, calcium, oxalate, phosphorus, and creatinine, therefore L. judaicus is effective in inhibition of urinary stones formation. Histopathologic results showed a decline of urinary stones in L. judaicus groups in comparison with ethylene glycol group.